Exploring the best industry practice of shariah review function under shariah governance framework 2010 / Athirah Qistina Azlan Shah - Azlan Shah, Athirah Qistina (2019)
Shariah Governance Framework introduced by Bank Negara Malaysia (BNM) stood firmly on the foundation of Shariah compliance and risk platform, with Shariah risk management, Shariah research, Shariah audit and Shariah review as the mechanisms to ensure Shariah compliance in the operations and business activities of the Islamic financial institution. The objective of this paper is to investigate the understanding of Shariah review function among Heads of Shariah review department from selected Islamic financial institutions (IFIs), which are Bank Islam Malaysia Berhad, CIMB Islamic and Bank Simpanan Nasional. The second objective is to identify the arrangements of Shariah Governance Framework model in the respective IFIs particularly on Shariah review function. Moreover, this research analyses the methodology, challenges and problems faced by the IFIs in managing Shariah review function with the provisions in Shariah Governance Framework in the respective IFIs. Finally, this research explores the best industry practice in the management of Shariah review function as stipulated under the Shariah Governance Framework. The qualitative method is adopted, where the information on the Shariah review practices of three Islamic banks in Malaysia is gained through semi-structured interviews conducted with the Heads of Shariah review department of selected IFIs. Apparently, this paper discovered that each of IFIs in Malaysia adopted the Shariah Governance Framework in different set-up because of the flexibility given by regulator to the IFIs and other factors such as nature and the size of the IFI. Additionally, it is found that all of the selected IFIs adopted the same methodology on managing Shariah review function in their institution. Lastly, based on the findings and analysis from the interviews, a proposed model of Shariah Governance Framework is presented to enhance the independency and effectiveness of Shariah review function is recommended to Bank Negara Malaysia and industry players.